2010
DOI: 10.1016/j.enpol.2010.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency interventions in UK higher education institutions

Abstract: Abstract:This paper provides an insight into energy efficiency interventions studies, focusing on issues arising in UK higher education institutions (HEIs) in particular. Based on a review of the context for energy efficiency and carbon reduction programmes in the UK and the trends in higher education sector, existing external and internal policies and initiatives and their relevant issues are extensively discussed. To explore the efficacy of some internal intervention strategies, such as technical, non-techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 4 publications
0
60
0
1
Order By: Relevance
“…This is largely because they are significant contributors to an organization's carbon emissions and are usually under direct control [19]. Altan [20] provides insights into energy efficiency and carbon reduction interventions in the UK HEIs. The efficacy of some intervention strategies such as technical, non-technical and management are explored, which is a demonstration of the need for a joint approach.…”
Section: Organizations and Carbon Managementmentioning
confidence: 99%
“…This is largely because they are significant contributors to an organization's carbon emissions and are usually under direct control [19]. Altan [20] provides insights into energy efficiency and carbon reduction interventions in the UK HEIs. The efficacy of some intervention strategies such as technical, non-technical and management are explored, which is a demonstration of the need for a joint approach.…”
Section: Organizations and Carbon Managementmentioning
confidence: 99%
“…The learning environment in the higher institutions is generally different from the primary or secondary education Every higher institution is built to serve the tertiary education to students based on the various programmes offered and therefore, the design and facilities provided in the higher institutions must suit the objectives of the education programmes However, the assessment of the building condition does not explicitly address the educational inadequacy of the academic buildings that are the relationship between the physical condition of the schools and the various educational goals and activities that take place within the building (Doidge, 2009) Problems in educational buildings include various aspects such as building designs, technical building elements, rooms, facilities, safety aspects, indoor and outdoor environmental problems and noise pollution According to Altan (2010), the increasing number of students and learning activities in higher institution has contributed to the inefficient of energy use and these may decrease the total performance system of the building year by year There are many terms used in evaluating the building performance However, O'Sullivan et al (2004) asserted that most building performance assessment is done at the design stage of a building through the use of simulation tools, some assessment is carried out at the construction and commissioning stage by means of commissioning tests O' Sullivan et al (2004) added that thereafter, there is little or no assessment carried out at the operation and maintenance phases of a buildings lifecycle Many building practitioners are not aware of the requirement of building evaluation after it is occupied Despite many research done towards building performance in higher educational buildings, the standard guideline of the building rating tool towards improving students' learning efficiency is not yet introduced in Malaysia Many studies are delineated to the environmental conditions of the building, such as visual aspects, thermal comfort and air movement, but, none of the research is merely done on the technical aspects of the building element (superstructure and architectural elements)…”
Section: Issue Statementmentioning
confidence: 99%
“…The construct indicators were initially compiled from the existing performance and green rating tools and also precedent research relating to building performance [2], [7], [8], [10]- [12], [17], [26]- [29].…”
Section: The Construct Of Performance-risk Indicators (Pri)mentioning
confidence: 99%
“…To optimise the performance of HEB, it should avoid allocating the occupants, visitors and passers-by at risk [6]. Several studies have shown that poor building performance presents vulnerability of risk towards the safety and health of building users [2], [7]- [13]. This demonstrates the significance of addressing risk in the building performance evaluation.…”
Section: Introductionmentioning
confidence: 99%